Maternal and fetal outcomes of pregnant women with pulmonary arterial hypertension associated with congenital heart disease in Beijing, China: A retrospective study. (22nd April 2022) - Liu, Yang; Li, Yanna; Zhang, Jun; Zhang, Dawei; Li, Jiachen; Zhao, Yichen; Liu, Kemin; Ma, Xiaolong; Bai, Chen; Gu, Hong; Fan, Xiangming; Wang, Jiangang
Abstract: As pulmonary arterial hypertension associated with congenital heart disease (PAH‐CHD) may increase maternal and fetal risk, this study explored the pregnancy outcomes of Chinese women with PAH‐CHD. The clinical data of pregnant women with PAH‐CHD admitted to the Beijing Anzhen Hospital from 2010 to 2019 were retrospectively analyzed; these patients and their offspring were followed up, with a mean period of 5.9 ± 2.7 years. Overall, 260 patients with PAH‐CHD were included. The mean maternal age was 27.7 ± 4.1 years, and 205 (78.8%) patients were nulliparous. The estimated systolic pulmonary artery pressure was 40–50 mmHg in 34.6% of the patients, 50–70 mmHg in 23.1%, and >70 mmHg in 42.3%. More than 96% of patients were diagnosed with PAH‐CHD before pregnancy. During pregnancy, heart failure occurred in 19.2% of the patients. Cesarean delivery was performed in 88.1% (15.0% emergency) of the patients. Complications included fetal distress (5.8%), preterm delivery (34.2%), and low birth weight (33.8%). A total of 15 mothers (5.8%) died, with the highest mortality rate in those with Eisenmenger syndrome (10/43, 23.3%), and 10 offspring died (3.8%), two (0.8%) following hospital discharge and eight (3.1%) while in hospital. Although most pregnant women with PAH‐CHD were able to have children, PAH increased the maternal and fetal risk. Thus, an individualized risk‐based approach with shared decision‐making may be more appropriate in pregnant women with PAH‐CHD.